2009
DOI: 10.1093/cercor/bhp058
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Mechanisms for Online Control of Hand Movement Trajectory: The Role of the Posterior Parietal Cortex

Abstract: The parietal mechanisms for the control of hand movement trajectory were studied by recording cell activity in area 5 of monkeys making direct reaches to visual targets and online corrections of movement trajectory, after change of target location in space. The activity of hand-related cells was fitted with a linear model including hand position, movement direction, and speed. The neural activity modulation mostly led, but also followed, hand movement. When a change of hand trajectory occurred, the pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
92
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 39 publications
15
92
0
Order By: Relevance
“…Previous studies on motor (Georgopoulos et al, 1983) and parietal (Archambault et al, 2009) cortex based on a double-step task similar to the one presented here have shown that cells in these areas change their activity pattern in such a way that neural modulation after the target jump and during hand movement to the second target is qualitatively similar to that observed when the hand makes a single movement from the center to the second target. This observation was used in our study as a starting point to perform additional quantitative analyses.…”
Section: Reconstruction Of Neural Activity Patterns Of Corrected Reacsupporting
confidence: 67%
See 4 more Smart Citations
“…Previous studies on motor (Georgopoulos et al, 1983) and parietal (Archambault et al, 2009) cortex based on a double-step task similar to the one presented here have shown that cells in these areas change their activity pattern in such a way that neural modulation after the target jump and during hand movement to the second target is qualitatively similar to that observed when the hand makes a single movement from the center to the second target. This observation was used in our study as a starting point to perform additional quantitative analyses.…”
Section: Reconstruction Of Neural Activity Patterns Of Corrected Reacsupporting
confidence: 67%
“…The classification was based on the use of modulation indices obtained across different tasks and epochs, as well as on bootstrapping procedures (Archambault et al, 2009). See supplemental material (available at www.jneurosci.org) for details.…”
Section: Cell Classificationmentioning
confidence: 99%
See 3 more Smart Citations